Relationships of Sociodemographic Characteristics with Glycemic Control and Dietary Adherence in Adults with Type 2 Diabetes - Tariq Al-Dwaikat; Diane Chlebowy; Timothy Crawford; Haitham Khatatbeh (Jordan University of Science and Technology, 2023)
Background: Previous studies supported that sociodemographic characteristics are significantly associated with dietary adherence and glycemic control in adults with T2D. The American Diabetes Association (ADA) recommends that individually designed nutritional plans consider the sociodemographic characteristics of the patients. Few studies were conducted to examine the impact of sociodemographic characteristics on adherence to the ADA dietary guidelines and A1C in adults with T2D. Aim: The study aimed to examine the relationships of sociodemographic characteristics with adherence to ADA dietary guidelines and glycated hemoglobin (A1C) in adults with type 2 diabetes (T2D). Methods: A cross-sectional study used data for 1,401 adults that were extracted from the National Health and Nutrition Examination Survey conducted between 2007 and 2012. Results: A large percentage of the sample was non-Hispanic White and female. Sex, race/ethnicity, marital status, education, and income were significantly related to A1C. Race/ethnicity and marital status were significantly related to adherence to ADA dietary guidelines. Single participants were at greater odds of being non-adherent compared to married participants. Furthermore, non-Hispanic Whites had much lower odds of non-adherence to ADA dietary guidelines compared to Hispanics. Conclusion: Individualizing patients’ nutritional plans based on sociodemographic characteristics is crucial for improving glycemic control and health outcomes in patients with T2D.